DAMD-PCR: A MINISATELLITE DIRECTED POLYMERASE CHAIN REACTION FOR SIDERITIS GENOTYPING STUDIES - Ince, A. G.; Karaca, M.; Turgu, K.; Onus, A. N. (African Journal of Traditional, Complementary and Alternative Medicines, 2009)
The genus Sideritis comprises approximately 150 species distributed chiefly in the Mediterranean region. Sideritis is represented by 53 taxa and 39 of which endemic to Turkey. Sixteen of these species naturally grow in Antalya, Turkey and six of them are endemic to this region in which this study was conducted. Some species of Sideritis are used as tea, flavouring agents and for medicinal purposes in many countries. The use of DNA markers will enhance Sideritis genetic studies for sustainable cultivation, preservation and germplasm analysis. DNA markers are valuable for plant breeders and taxonomist since they offer an effective way to identify genotypes. Repetitive DNA sequences such as microsatellites, minisatellites, midisatellites and satellites can be of great value in assessing a high level of polymorphism as they distributed throughout the genomes analyzed so far. In the present study a polymerase chain reaction (PCR) method, known as the directed amplification of minisatellite region DNA (DAMD-PCR), an inexpensive, PCR-based method was evaluated to amplify minisatellite DNA regions of six different species of Sideritis using 12 minisatellite core specific primers which obtained from different organisms. Analyses indicated that the use of minisatellite core specific primers showed higher polymorphism information content values ranging from 55.6% to 91.4%. Higher level of polymorphism information content values and repeatability of the PCR banding patterns among the Sideritis species used in the present study clearly showed that Sideritis species contain a wide range of genetic diversity and DAMD-PCR technique is a powerful technique for Sideritis genotyping studies.